Microalgaes in the treatment of wastewater from the curtiembres industry - Jácome-Pilco, Carlos (2021)
The wastewater from the tanning industry has high concentrations of heavy metals, especially chromium (Cr), as well as other components such as Nitrites, Nitrates, Phosphates, and sulfates, which, if not treated prior to discharge, can seriously alter the quality of surface water bodies. Thus, an alternative treatment to these industrial effluents has been proposed in various investigations. In this sense, the objective of this work was to carry out a detailed bibliographic review on the use of microalgae to treat wastewater from tanneries. For which, 42 papers between scientific articles and theses with international index were analyzed, all of them related to the subject of work. After the analysis, the most widely used microalgae in bioremediation processes in this type of industry are: Scenedesmus sp, Spirulina sp, Chlorella sp, Tetraselmis sp, and Pseudochlorella sp., Important for their high efficiency in removing Chromium, and others polluting elements; where, the genus Scenedesmus and Spirulina demonstrated an efficiency greater than 85% of Cr removal, followed by Chlorella and Pseudochlorella (> 60%). In the removal of nitrates and nitrites, the genus Scenedesmus, showed better levels of removal (90%), followed by Chlorella and Pseudochlorella (65%). Regarding the removal of Phostates and Sulfates, the genera Chlorella and Pseudochlorella were the type of algae that showed a removal level of 100%, followed by Tetraselmis, Scenedesmus and Tetraselmis (> 95%). This consortium of micro algae could be good alternatives to conventional treatment methods for the leather industry.